OPTIMIZING PANGLIMA LAOT IN MARITIME DISPUTE RESOLUTION IN LHOKSEUMAWE CITY - Budi Bahreisy; Hidayat Hidayat; Ferdy Saputra (NOMOI Law Review, 2022)
The existence of Panglima Laot in Aceh apart from being a social leader of the customary community legal alliance, is also an Alternative Dispute Resolution (APS) institution. The juridical basis of its position is contained in Law No. 11 of 2006 concerning the Government of Aceh, its implementing regulations are in the form of Aceh Qanuns such as Aceh Qanun No. 9 of 2008 concerning the Guidance of Customary Life and Customs, and Aceh Qanun No. 10 of 2008 concerning Customary Institutions . Based on the description on the background above, in this legal research it can be formulated how the position of Panglima Laot as a marine dispute resolution institution in the legal system in Indonesia and whether Panglima Laot is optimal as an institution in maritime dispute resolution in Lhokseumawe City . This research is an empirical legal research with a qualitative approach that uses primary data and secondary data. In obtaining primary data, respondents and informants were determined. The new positive law will have an effective force if it contains, or is in harmony with the laws that live in society. The focal point of legal development is not in laws, judge decisions, or legal science, but in society itself.